Dimensões da sustentabilidade e a sua apropriação pelas entidades da sociedade civil e pela administração municipal. Caso: projeto Jaboticabal sustentável. - Silva, Antonio Sergio da (2005)
Nowadays necessity exists to accomplish alternative experiences that go through the democratic participative processes on the politics considered like a refering set marker because they contribute to the construction of new relationships in the public spaces of participation between the society and the power heading for a more sustainable society. Then the objetive of this research was to analyze the relationships between the entities of the organized civil society and the local public administration in the participation by the perspective of the sustainability dimension which are determining at the practice of the participation space to leave from a pilot experience called Sustainable Jaboticabal Project accomplished at Jaboticabal, State of São Paulo. The unit of analisys was the Sustainable Jaboticabal Group Action composed by entities of the civil society and the municipal government's representatives during the collective activities. The results were obtained through reports of activities, accomplishment of interviews and the researcher's observation. The public administration assumed the function of provider and its action were centralized at the environmental dimension and limited the development of the political dimension by restriction on the participation ways. The collective construction of the knowledge about sustainable favored the understanding of the participative processes for the transformation of the political culture. The environmental dimension was like a determining in the relationships between the entities; the entities of the civil society adopted the political dimension before the centralization of the administration; the dimension of the sustainable not incorporated by public administration was the politics. In this case, the political dimension of the sustainable is decisive in the relationships to reach the sustainable. The nullity or the unilaterality of the political dimension in the relationships between entities of the organized civil society and the public administration it weakens transdimensionality which is present at the centrality of the political dimension of the sustainability because it is on this dimension that the synergy and the resonance of the actions devise in the different dimensions are anchored and then moulding own sustainability. The political dimension itself presents like shaft leader in the relationships to reach the sustainability.